Diversity of Anatomical Morphological Characters of Leaves of Mangrove Plant Types In Panimbang Banten - Nabilah, Amanda; Suyamto, Suyamto; Mu’jijah, Mu’jijah (Biology, Medicine, & Natural Product Chemistry, 2025)
Mangroves are plants that produce seeds (spermatophyta), mangroves also have many benefits, namely as an economic or ecological function. Mangrove plants have different types of leaf shapes. Leaves have the task of absorbing nutrients and gases, as well as processing food through the process of photosynthesis. This study aims to determine the differences in leaf shape based on morphological and anatomical characters. The method used is exploration and preparation of preserved preparations. The samples used were some mangrove leaves found in Panimbang District. The stages of the research are starting with taking the third leaf sample, observing the morphological characters of the leaves, taking samples. Parameters used to observe morphological characters were leaf shape, base shape, leaf tip, leaf length, width and length of petiole. Anatomical character of shape and number of stomata, shape and length of palidase.